2000
DOI: 10.1364/josaa.17.000304
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion control with use of long-period fiber gratings

Abstract: Chirped long-period fiber gratings are analyzed for management of dispersion in optical fiber communications systems. A ray model is used to derive simple analytic expressions that describe the transmission, chromatic delay, and dispersion properties of chirped long-period fiber gratings. A numerical model based on coupled-mode theory is used to verify the accuracy of the analytic expressions and explore design issues of the chirped long-period grating. With certain reasonable restrictions, chirped long-period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…In optical telecommunications include bandpass filters, tunable filters, variable attenuators, mode converters and dispersion compensators [1][2][3]. In sensor technology are used in the measurement of pressure, temperature, strain, measurement in structures or refractive index of liquid [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In optical telecommunications include bandpass filters, tunable filters, variable attenuators, mode converters and dispersion compensators [1][2][3]. In sensor technology are used in the measurement of pressure, temperature, strain, measurement in structures or refractive index of liquid [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…LPGs consist of a periodic perturbation in optical fiber refractive index which is able to, at specific wavelengths, partially couple light that propagates in the fundamental core mode to co-propagating cladding modes [3]. Such cladding modes can have interesting chromatic dispersion characteristics [4,5] or, more generally, be used for sensing applications. Grating transmission spectrum, which is characterized by attenuation bands due to the high loss experienced by the cladding modes, can be used to sense parameters such as temperature, LPG surrounding medium refractive index and fiber bending curvatures [6].…”
Section: Introductionmentioning
confidence: 99%
“…The methods of design and manufacture have been put forward [3–5]. While fiber Bragg grating (also called short‐period fiber grating) has shown excellent capability of backward reflection with adjustable bandwidth [6], long‐period fiber grating (LPG) is sensitive to different environmental parameters [7] and of great dispersion character [8]. Recent study has shown that Ultra‐long‐period fiber grating (ULPG), with the period of several millimeters, takes the merit of multiparameter measuring through peaks coupled by its different diffraction orders [9].…”
Section: Introductionmentioning
confidence: 99%